2006
DOI: 10.1016/j.otohns.2006.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA‐DR3 and HLA‐DR4 with Sinonasal Polyposis in Mexican Mestizos

Abstract: B-2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…45, 46, 57, 80-84 However, there remains no consensus, as few attempts have been made to replicate these associations. To give one example of the complexity of comparing studies, the haplotype HLA-A1/B8 has been examined in two populations, a case series of 29 CRSwNP subjects from the United Kingdom (UK) by Moloney et al 81 and an Austrian case-control study of 89 CRSwNP subjects and 1070 controls by Luxenberger et al 80 Neither study found HLA-A1/B8 to be associated with CRSwNP itself.…”
Section: Genetics Of Crs: Current State Of the Field And Limitations mentioning
confidence: 99%
See 3 more Smart Citations
“…45, 46, 57, 80-84 However, there remains no consensus, as few attempts have been made to replicate these associations. To give one example of the complexity of comparing studies, the haplotype HLA-A1/B8 has been examined in two populations, a case series of 29 CRSwNP subjects from the United Kingdom (UK) by Moloney et al 81 and an Austrian case-control study of 89 CRSwNP subjects and 1070 controls by Luxenberger et al 80 Neither study found HLA-A1/B8 to be associated with CRSwNP itself.…”
Section: Genetics Of Crs: Current State Of the Field And Limitations mentioning
confidence: 99%
“…45, 46 In a study of Mexican Mestizos (defined as having mixed Native American [56%], European [40%], and African [4%] ancestry) involving 34 CRSwNP patients and 99 controls, Ramirez-Anguiano et al 45 found the HLA-DRB1*04 allele was significantly associated with CRSwNP (odds ratio [OR]=2.2, 95% confidence interval [CI]=1.2-4.2, P = .009). However, a Turkish study of 66 CRSwNP patients and 100 controls by Keles et al 46 did not find HLA-DRB1*04 to be more frequent in CRSwNP patients compared to controls (allele frequency [AF] in CRSwNP=23.4%, AF in controls=23.4%, P > .05).…”
Section: Genetics Of Crs: Current State Of the Field And Limitations mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, HLA-DRB1 genes have been involved in asthma severity in children [5, 6] and susceptibility to occupational asthma [7] and allergic bronchopulmonary aspergillosis [8]. They are implicated also in nasal polyposis and, in particular, the HLA-DRB1∗04 allele has been associated with sinonasal polyposis in a study on the Mexican Mestizo population [13] and in a group of Turkish patients with nasal polyposis, asthma, and aspirin salicylic acid triad [14]. …”
Section: Resultsmentioning
confidence: 99%